GENDER INEQUALITY AND FEMINISM IN ARUNDHATI ROY’S THE GOD OF SMALL THINGS - Rima Mardiyani; Tatan Tawami (MAHADAYA: Jurnal Bahasa, Sastra, dan Budaya, 2022)
This research aimed to analyses feminism and gender inequality in the novel The God of small things by Arundhati Roy. The writer aims to reveal the types of feminism, gender inequalities are reflected in the novel. In this research, gender inequality theory is used to determine the types of gender inequality experienced by the characters in the novel God of Small Things, beside of that, feminism theory is used to show how women can overcome gender inequality. Furthermore, this paper uses a qualitative descriptive method. The data is gathered through quotations from the book, and the analysis is backed up by the book and the journal. The base theory is based from what types of feminism type and what kind of gender inequality, the type of gender inequality that experienced by woman including stereotypes, violence, marginalization, double burden and subordination and there are four feminism movements ideology, which are liberal feminism, radical feminism, Marxist feminism, and socialist feminism. Besides that, in this research the author discovered three kinds of gender inequality experienced by women: violence as the part of radical feminism, marginalization as the part of liberal feminism, and subordination as the part of socialist feminism. As the result of this research is to show and identifying what kind of gender inequality and feminism according to the theory. Keywords: Feminism, Gender inequalities, Patriarchy